The Efficacy and Psychoneuroimmunology Mechanism of Camouflage Combined With Psychotherapy in Vitiligo Treatment - Chang, Yuqian; Zhang, Shaolong; Zhang, Weigang; Li, Shuli; Li, Chunying (Frontiers in Medicine, 2022)
Background and Objectives: The efficacy of camouflage combined with psychotherapy and the underlying mechanism is poorly understood in vitiligo management. This study was to investigate the joint efficacy and further explore the psycho-neuro-endocrine-immune-skin interactions. Patients and methods: In a prospective, non-randomized and concurrent controlled trial, patients were divided into two groups. The quality of life was evaluated using the Vitiligo Life Quality Index of the Chinese version. Serum levels of neuropeptides and cytokines were detected by enzyme-linked immunosorbent assay. Results: 149 patients were included. After treatment for 4 weeks, the total and subcategory quality of life scores in the intervention group were much lower than those in the control group. Serum levels of neuropeptide-Y and melanin-concentrating hormone significantly decreased, meanwhile adrenocorticotropic hormone increased in both active and stable patients of the intervention group, but not in the control group. In addition, serum levels of interferon-γ, CXC chemokine ligand 10 and interleukin-1β decreased in both the active and stable patients of the intervention group, but only in the active patients of the control group. Conclusions: The combination of camouflage and psychotherapy provided a clinically meaningful reduction in quality of life and ameliorated the outcome by modulating the psycho-neuro-endocrine-immuno-skin system during vitiligo management. Clinical Trial Registration: NCT03540966 (https://clinicaltrials.gov/ct2/show/NCT03540966)